Attitude is everything : change your attitude change your life - Jeff Keller (Gurgarm Harper Collins Publishers India, 2017)
IF YOU CAN DREAM IT, YOU CAN DO IT!Do you dread going to work? Do you feel tired, unhappy, weighed down? Have you given up on your dreams? The road to a happier, more successful life starts with your attitude--and your attitude is within your control.Whether your outlook is negative, positive or somewhere in between, Jeff Keller, motivational speaker and coach, will show you how to take control and unleash your hidden potential through three powerful steps:--THINK! Success begins in the mind. The power of attitude can change your destiny.--SPEAK! Watch your words. How you speak can propel you towards your goals.--ACT! Don't sit back. Take active steps to turn your dreams into reality.Soon, you will be energized and see new possibilities. You will be able to counter adversities and develop talents unique to you. Your relationships will improve, both at work and in your personal life. All you need is this step-by-step programme to change your attitude and your life!
Keywords: Personality Development; Success Begins in the mind